(untitled) (REMUNOM, 2025)
It is essential to foster new knowledge linked to a professional teaching culture in which the development of teaching materials is established in a more autonomous and contextual way. When it comes to teaching Portuguese, consolidating pedagogical autonomy involves increasing access to digital media that provide teachers with content and resources to create more personalized teaching materials that are suited to the specific needs of their students. In this sense, given the lack of access teachers have to varied quality teaching materials, as well as the difficulties in understanding the guidelines of the BNCC in order to create teaching tools based on this document, this work proposal, based on the theoretical foundations of Bakhtinian dialogism, sets itself the general objective of contributing to research in the field of applied linguistics through the development of an educational application that assists in the development of teaching materials for the teaching of Portuguese language in basic education. The methodology used in the research project entitled “Educational application for the creation of teaching material for Portuguese as a mother language”, in which we bring the discussions to this article, was inspired by Design Thinking, that is, an interactive approach centered on people and problem solutions (BROWN; WYATT, 2010; BROWN, 2017). The expected results include the realization of the students’ teaching identity and the app’s support for the development of learning objectives for Portuguese language teaching.